Mixing Insulating Commodity Polymers with Semiconducting n-type Polymers Enables High-Performance Electrochemical Transistors - Zeglio, Erica (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.